Aumento dell'espressione di marker di apoptosi ed autofagia in ostriche concave (Crassostrea gigas) allevate nel Medio Adriatico durante un periodo di mortalità - Galosi, L.; Roncarati, A.; Gennari, L.; Tosi, F.; Gastaldelli, M.; Arcangeli, G.; Rossi, G.; Mariotti, F.; Magi, G. E. (SIRAM, 2019)
As part of an Eureka project, 1 batch of cupped oyster (Crassostrea gigas) raised in Adriatic Sea, was studied, during a period with high mortality rate, in order to understand the pathogenesis of the mortality. Immunohistochemical analysis were performed to evaluate the expression of markers of cell death as active Caspase-3 for apoptosis and LC3b for autophagy. Molecular analysis for Ostreid Herpesvirus-1, Vibrio aestuarianus and Vibrio splendidus were also done. During the late summer until October a high mortality rate was reported and the oysters highly expressed both apoptosis and autophagy markers, compared to the beginning of the summer season, in the digestive gland. In the same specimens strongly expressing apoptosis and autophagy markers, high quantity of Vibrio splendidus was detected.